1998
DOI: 10.1111/j.1469-8749.1998.tb15382.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of preterm infants in the intensive‐care unit to predict cerebral palsy and motor outcome at 6 years

Abstract: One hundred and fifty-three infants were assessed by a method specitlc to preterm infants and appropriate to the intensive-care nursery environment. The presence or absence of six atypical features (coarse jitters. dominant asymmetrical tonic neck reflex, paucity of movement, 'contradictory' development, hypotonia, or hypertonia) resulted in neonatal classi5cation. There were 116 'usual' (an absence of atypical features with progressive development), 26 'unusual' (a transient occurrence of any atypical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…GMDS-ER locomotor scores at 2 years were significantly higher for infants classified as usual than those classified as monitor ( p = 0.003), demonstrating significantly less motor delay (2.00 months versus 6.00 months; p = 0.001). These results support previous findings, in which infants within the ‘suspect’ LAPI group showed significantly lower scores than the ‘usual’ group on the Touwen motor assessment at 6 years of age, for all motor subsets including balance, co-ordination and fine-motor skills ( p < 0.05) [ 11 ]. Linear regression analysis found a predicted delay of 3.58 months for infants classified as monitor, after accounting for the effects of GA, BW, presence of NEC, CLD and genetic abnormalities.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…GMDS-ER locomotor scores at 2 years were significantly higher for infants classified as usual than those classified as monitor ( p = 0.003), demonstrating significantly less motor delay (2.00 months versus 6.00 months; p = 0.001). These results support previous findings, in which infants within the ‘suspect’ LAPI group showed significantly lower scores than the ‘usual’ group on the Touwen motor assessment at 6 years of age, for all motor subsets including balance, co-ordination and fine-motor skills ( p < 0.05) [ 11 ]. Linear regression analysis found a predicted delay of 3.58 months for infants classified as monitor, after accounting for the effects of GA, BW, presence of NEC, CLD and genetic abnormalities.…”
Section: Discussionsupporting
confidence: 91%
“…Marcroft et al [ 10 ] similarly reported a high specificity of 89% (95% CI 71% to 98%), with wider CI due to the smaller sample size. Very high specificity of 98% was reported by Lacey and Henderson-Smart [ 11 ] and Lacey et al [ 9 ], when comparing with neuromotor outcomes at 3 and 6 years old, perhaps due to a more robust diagnosis of CP at this later age when transient abnormal motor signs present in the first few years have resolved.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation